Meiotic defects in the Arabidopsis rad50 mutant point to conservation of the MRX complex function in early stages of meiotic recombination. - Bleuyard, J; Gallego, M; White, C (2004)
The Rad50, Mre11 and Xrs2/Nbs1 proteins, which form the highly conserved MRX complex, perform a wide range of functions concerning the maintenance and function of DNA in eukaryotes. These include recombination, DNA repair, replication, telomere homeostasis and meiosis. Notwithstanding the attention paid to this complex, the inviability of vertebrate rad50 and mre11 mutants has led to a relative lack of information concerning the role of these proteins in meiosis in higher eukaryotes. We have previously reported that Arabidopsis atrad50 mutant plants are viable and that atrad50 mutant plants are sterile. The present study reports an analysis of the causes of this sterility and the implication of the AtRad50 protein in meiosis. Both male and female gametogenesis are defective in the Arabidopsis atrad50 mutant and cytological observation of male meiosis indicates that in the absence of the AtRad50 protein, homologous chromosomes are unable to synapse. Finally, the atrad50 mutation leads to the destruction of chromosomes during meiosis. These phenotypes support a role for the Arabidopsis MRX complex in early stages of meiotic recombination.